On Reliable Transmission of Data over Simple Wireless Channels - Gburzynski, Pawel; Kaminska, Bozena; Rahman, Ashikur (Journal of Computer Systems, Networks, and Communications, 2009)
Standard protocols for reliable data transmission over unreliable channels are based on various Automatic Repeat reQuest (ARQ) schemes, whereby the sending node receives feedback from the receiver and retransmits the missing data. We discuss this issue in the context of one-way data transmission over simple wireless channels characteristic of many sensing and monitoring applications. Using a specific project as an example, we demonstrate how the constraints of a low-cost embedded wireless system get in the way of a workable solution precluding the use of popular schemes based on windows and periodic acknowledgments. We also propose an efficient solution to the problem and demonstrate its advantage over the traditional protocols.